Senyawa Goitrogenik dalam Bahan Makanan (Goitrogenik Substances in Foodstuffs) - DEWI, YULIA LANTI RETNO (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2015)
It has been known for a long time that iodine deficiency results in enlarged thyroid gland (goiter). However, iodine supplementation alone frequently fails to eliminate goiter in particular area. At present, experts realized that many agents interact with iodine deficiency in producing goiter. Agents that cause goiter are known as goitrogens. Several goitrogens are found in the foodstuff. Our study in Ngargoyoso sub-district revealed that several foods containing suspected such substances are consumed by school children. They are soybean cake, tofu, onion, tomato, cassava leaves, cabbage, cassava tuber and broccoli. Soybean cake and tofu are made from soybean containing isoflavone which exerts anti-thyroid activity in rats. Onion contains allyl-sulfides. Tomato, cassava leaves, and broccoli contain pigments with antioxidant moiety and anti thyroid activity. Cabbage contains isothyocyanat, a potent anti thyroid in rats and rabbits. Cassava contains linamarin. The study was a recalled study using food frequency questionnaire. In order to prove the goitrogenic activity in those foods an In-Vitro Assay or In-Vivo Assay should be carried out. Since plants grown in certain areas are influenced by soil and water, it is reasonable to measure anti thyroid activity using plants grown locally. This paper will describe those assays and suggest the most applicable in Indonesia.